Punishment for intentions or outcomes: the role of gender and social norms - Simon Dato; Tim Friehe (Social Choice and Welfare, 2025)
Individuals often evaluate others' actions based on both their perceived intentions and their resulting outcomes, rewarding favorable actions and punishing unfavorable ones. This study aims to isolate the influence of these factors on punishment. We experimentally demonstrate that, when outcomes are held constant, second movers punish first movers who choose selfish actions more severely than those who select considerate ones. Conversely, when intentions are fixed, the severity of punishment does not significantly differ between fair and unfair outcomes on average. However, this average masks gender-specific variations. Men tend to prioritize punishing unkind intentions, while women are more sensitive to the perceived fairness of outcomes. Social norms help explain punishment choices and gender differences.
Keywords: 330